Pengaruh Substitusi Tepung Beras dengan Tepung Jagung (Zea mays.L) terhadap Karakteristik Kimia dan Mutu Organoleptik Kue Onde-onde. - Adimarta, Trian; Nopriyanti, Marisa; Sapitri, Lisa (Politeknik Negeri Ketapang, 2023)
His study aims to determine the value of water content and ash content in ondeonde and to determine the level of panelist acceptance of the manufacture of ondeonde substitution of rice flour with corn flour (Zea Mays.L) based on organoleptic tests of color, texture and taste. The method of making onde-onde is with 3 treatments. Treatment 1 (75% rice flour: 25% corn flour), treatment 2 (50% rice flour: 50% corn flour), treatment 3 (25% rice flour: 75% corn flour) ), while glutinous rice flour is a fixed variable, namely 200 grams of glutinous rice flour, then mixing the ingredients, and frying at ± 170°C for 5 minutes. The results of the analysis of water content and ash content in onde-onde products showed that the best treatment was found in treatment 1 substitution of 75% rice flour: 25% corn flour with a water content value of 23.73% and an ash content of 0.22%, p. has complied with the stipulated SNI. Based on the results of organoleptic tests with 30 untrained panelists on the parameters of color, texture, and taste, it was found that the best treatment was in treatment 3, namely with a ratio of 25% rice flour: 75% corn flour with a brownish color, very soft texture, very soft texture, and very strong taste. Like.